1994
DOI: 10.1111/j.1440-169x.1994.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A‐Mediated Homeotic Transformation of Tail to Limbs, Limb Suppression and Abnormal Tail Regeneration in the Indian Jumping Frog Polypedates maculatus

Abstract: In this study the effects of vitamin A on tadpoles of Polypedates maculatus with an amputated tail were investigated. After amputation of half the tail at the hindlimb‐bud stage, tadpoles were exposed to vitamin A (palmitate) 10 IU/ml solution for 24 hr (Group I), 48 hr (II), 72 hr (III), 96 hr (IV), 120 hr (V) or 144 hr (VI). Vitamin A was deleterious to survival of the tadpoles since 10, 30 and 30% tadpoles died from Group IV, V and VI, respectively before the emergence of forelimbs. Regeneration of the tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…This effect of hypervitaminosis A has been known for a long time to occur in adult tissues (Wolf & Johnson, ; Penniston and Tanumihardjo, ), embryonic and regenerative processes (Ju et al, ). The disorganization of muscle cells observed in the present study was also seen in toad tadpoles treated with vitamin A (Mahapatra and Mohanty‐Hejmadi, ). The invasion of tissues with blood cells and phagocytes, likely derived from the disruption of endothelial walls of blood vessels, indicate lysosome activation and cell destruction by apoptosis (pycnosis) but also necrosis (cell degradation).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This effect of hypervitaminosis A has been known for a long time to occur in adult tissues (Wolf & Johnson, ; Penniston and Tanumihardjo, ), embryonic and regenerative processes (Ju et al, ). The disorganization of muscle cells observed in the present study was also seen in toad tadpoles treated with vitamin A (Mahapatra and Mohanty‐Hejmadi, ). The invasion of tissues with blood cells and phagocytes, likely derived from the disruption of endothelial walls of blood vessels, indicate lysosome activation and cell destruction by apoptosis (pycnosis) but also necrosis (cell degradation).…”
Section: Discussionsupporting
confidence: 82%
“…It has also been reported that long exposure to vitamin A has a number of teratogenic effects on the development of amphibians, including limb abortion and homeotic transformations of the tail into limbs (Maden, ; Niazi & Saxena, , 1994; Mahapatra and Mohanty‐Hejmadi, ). Teratological effects so pronounced were however not seen in our experiments, perhaps due to the short time of observations, less than 1 month after the beginning of tail regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies on amphibian tadpoles have shown that treatment of amputated tails with retinoids leads to inhibition of regeneration in Bufo andersoni (Niazi and Saxena, 1968), Notophthalmus viridescens, Ambyostoma maxicanum and X. laevis (Scadding, 1987). Further, in addition to inhibition of tail regeneration, ectopic supernumerary limbs generated at the amputated region were demonstrated in Uperodon systoma (Mohanty-Hejmadi et al, 1992), Polypedates maculates, B. melanostictus, Microhyla ornata and Rana tigrina (Mahapatra and Mohanty-Hejmadi 1994;Das and Dutta, 1996). The diff erence in results obtained in the present experiment compared with those of earlier workers may be attributed to diff erence in the vitamin A source, length of exposure and time of the exposure and the experimental design used (tadpoles were exposed to vitamin A only for fi rst fi ve days after amputation and then reared in conditioned water in the present study).…”
Section: Amputation Of Tail and Treatmentmentioning
confidence: 95%
“…Thyroid hormone is known to promote the amphibian metamorphosis in general (Hayes and Wu 1995;Opitz et al, 2006;Degitz et al, 2005;Oka et al, 2009) while retinoids (vitamin A/retinoic acid/palmitic acid) interfere with limb development and are known to induce homeotic transformation, leading to the appearance of ectopic limbs at the amputated end of the tail (Mahapatra and Mohanty-Hejmadi, 1994;Das and MohantyHejmadi 1998, 1999, 2003Hejmadi and Crawford, 2003). It has been reported that exposure of Xenopus laevis and Bufo bufo larvae to methoprene (an insect growth regulator) and its derivatives results in similar eff ects to those reported for vitamin A when the tail is amputated (Paulov, 1976;Degitz et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Amongst all the effects of vitamin A, the most amazing one on embryonic systems is the homeotic transformation of tails to limbs in the marbled balloon frog, Uperodon systoma [Mohanty-Hejmadi et al, 1992]. Subsequently a similar phenomenon was also confirmed in other species of tadpoles [Maden, 1993;Mahapatra and Mohanty-Hejmadi, 1994;Das and Dutta, 1996]. To understand the histological processes underlying the morphological changes it is necessary to comprehend the process of regeneration and homeotic transformation.…”
Section: Introductionmentioning
confidence: 99%